IMPLEMENTASI TOKEN ECONOMY SEBAGAI SARANA MOTIVASI KONSUMSI SAYUR MAYUR PADA ANAK USIA DINI - Mawarti, Awalina Fidiah; Umami, Lu’lu’ul (Jurnal CARE (Children Advisory Research and Education), 2013)
This research intend to know about effectiveness the implementation of token economy as tool of motivation to consuming vegetables for kids. This research made at Muslimat 01 Kindergarten, Malang. The subject in concerned this research took by purposive sampling and total of subject are eight students. Data technique analysis was used descriptive quantitative analysis. The result of this research indicate that token economy applicable to motivation consume vegetables for kids.Key words : Token economy,motivation, vegetables